Dietary exposure assessment of total mercury and methylmercury in commercial rice in Sri Lanka. (January 2020) - Xu, Xiaohang; Han, Jialiang; Abeysinghe, Kasun S.; Atapattu, Anjana J.; De Silva, P.Mangala C.S.; Xu, Zhidong; Long, Shuiting; Qiu, Guangle
Abstract: Methylmercury (MeHg) in rice has attracted growing health concern over the past decade, due to the accumulation of high MeHg levels, which may pose potential health risk to humans. Rice is the staple food in Sri Lanka; nevertheless, the presence of micro pollutants, such as MeHg has been not investigated. Therefore, commercial rice samples from the Sri Lankan market (n = 163) were measured to reveal the total mercury (THg) and MeHg levels. THg (mean: 1.73 ± 0.89 ng/g, range: 0.21–6.13 ng/g) and MeHg concentrations (mean: 0.51 ± 0.37 ng/g; range: 0.03–3.81 ng/g) were low. Compared to the fish MeHg exposure, the rice MeHg exposure was generally lower in different consumption groups, suggesting that rice plays a less role than fish in MeHg exposure in Sri Lanka. Babies (infants and toddlers) at one year old may face fish MeHg exposure (0.17 μg/kg bw/day) higher than the reference dose for MeHg (RfD)-0.1 μg/kg bw/day, which was more than 5 times that of rice MeHg exposure (0.031 μg/kg bw/day). Future studies in Sri Lanka should focus on health impacts under long-term overexposure of MeHg, especially in vulnerable populations. Some diet changes should be made to mitigate MeHg exposure levels in Sri Lankans. Highlights: We firstly carried a nationwide investigation of Hg in Sri Lankan commercial rice. THg and MeHg exposures in different rice and fish eating populations were assessed. Rice consumption plays less important role in MeHg exposure in Sri Lanka.